Decreasing rainfall frequency contributes to earlier leaf onset in northern ecosystems - Wang, Jian; Liu, Desheng; Ciais, Philippe; Peñuelas, Josep (Nature climate change, 2022)
Climate change substantially advances the leaf onset date (LOD) and regulates carbon uptake by plants. Unlike temperature, the effect of precipitation remains largely elusive. Here we use carbon-flux measurements, in situ records of leaf unfolding and satellite greenness observations to examine the role of precipitation frequency ( P freq , number of rainy days) in controlling the LOD in northern ecosystems (>30° N). Widespread decreases in P freq during the past three decades positively contributed to the advance in LOD, possibly due to increased exposure to radiation, exhibiting a dominant control of LOD over ~10% of the area. Lower P freq may also enhance chilling at night and warming at daytime, consequently leading to earlier LOD. We further develop a weighted precipitation growing-degree-day algorithm that projected a generally earlier LOD than currently predicted. These results highlight the need for a comprehensive understanding of the impacts of precipitation on LOD, which is necessary for improved projections. Changes in precipitation remains an understudied factor that can impact leaf onset date (LOD) under climate change. The authors show that decreasing precipitation frequency has contributed to LOD advancement, and that incorporating precipitation data projects earlier LOD than currently predicted.